THE METHODOLOGY AUTOMATION OF ERGONOMIC LEXICAL AND GRAMMATICAL ALGORITHMIZATION OF LATIN LANGUAGE DIFFICULTIES - N. A. Stadulskaya; L. A. Antipova; K. V. Martirosyan; V. F. Antonov (Современная наука и инновации, 2022)
In this message we have presented for the first time a "The methodology of ergonomic algorithmization of lexical and grammatical difficulties oflatin language", developed by the authors. The purpose of the methods is to study the most difficult grammatical and lexical phenomena by the visualization of textual forms and vice versa. We have demonstrated the application capabilities of information technologies for ergonomic algorithmization of lexical and grammatical difficulties of the Latin language methodology automatization